Effects of inducing g-jitter on mixed convection flow past an inclined stretching sheet - Noraihan Afiqah Rawi, 1991- author; Sharidan Shafie, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014